Marcella. Season one [videorecording (DVD)] - Friel, Anna, 1976-; Pinnock, Nicholas, 1973-; Panthaki, Ray, 1979- (RLJ Entertainment, 2017)
An emotionally damaged ex-police detective goes back on the job after her seemingly happy marriage falls apart to investigate a serial killer.